Effect of Guidelines Based Practice on Dialysis Complications in Patients on Permanent Hemodialysis - Amjad Ali, Adnan Yaqoob, Zunaira Aziz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hemodialysis patients experienced a number of issues that led to early session termination, decreased waste removal, and ultimately decreased dialysis effectiveness. The dialysis unit's nursing staff struggles to care for these patients. An updated practice guideline is needed to provide the proper interventions to lower complications and improve patient outcomes. Long-term maintenance hemodialysis has also changed the way that patients with end-stage renal failure are treated, reducing the risk of death. Objective: To assess the effect of guidelines based practice on dialysis complications in patients on permanent hemodialysis. Methodology: A single group quasi experimental conducted in Sheikh Zayed Hospital Lahore Punjab Pakistan from 1 June to 15 August 2022, data was collected Through the use of a self-structured tool from 30 people receiving hemodialysis for at least six months. The validity and reliability of the tool were initially assessed. A systematic instruction workshop was offered to care providers following the pre data, and the previously described criteria were reassess. Result: According to this study, there were 60% men and 40% female, had age between 30 to 39 (43.3%) and mostly 70% belong to urban area. The McNemar test evaluated the reduction between the pre- and post-dialysis fatigue, headache, vomiting, nausea, breathlessness and cramps with statistical significance (P<0.05). Practical implication: Patients receiving hemodialysis must need a complete nursing care in order to reduce dialysis induced complications. Conclusion: The significant reduction of dialysis complication after conducted dialysis on guideline base; it is recommended that dialysis be performed in accordance with the most recent clinical guidelines to improve hemodialysis procedures and boost hemodialysis efficacy. Keywords: Hemodialysis, Guidelines based practice and Dialysis Complications